Genetic diversity of meat quality related genes in Argentinean pigs - Rodríguez, Viviana Rita (2022)
Genetic influence on pork quality exists between breeds and within a breed. The variation is caused by a large set of genes, and pork quality traits have a multifactorial background. Research into the genetics of meat quality found causative mutations associated with marked effects on pig meat value. This study aimed to investigate the segregation of meat quality-related SNPs and compare their diversity and genetics in commercial and Creole pigs from different farms in the North-West of Argentina. A screen for SNPs in RYR1, PRKAG3, CAST, and SOX6 candidate genes and the differentiation of their genotypes by PCR–RFLP was conducted. All genes were characterized by a high level of polymorphism and heterozygosity, and populations showed no differences in the genetic structure for the analyzed SNPs. These results highlighted the role of pig genotypes as a source of basic variability potentially affecting processed meat products and fresh meat.